Uma Casa Portuguesa: as crianças austríacas em Portugal no pós-guerra (1947-1958) - Pinho, Ana R. da Silva (CEM – Cultura, Espaço & Memória, 2021)
Between 1947 and 1958, thousands of Austrian children were hosted by Portuguese families and institutions as part of an action promoted by Caritas. Thus escaping, for some time, the misery of a country devastated by war, these “Caritas children” found in Portugal, under Antonio de Oliveira Salazar’s Estado Novo, shelter and, in most cases, affection: an experience that, besides having repercussions in their memories and journeys, also left marks that, although less visible, continue to make themselves felt in Portugal. In this article we present a general outline of the research «The “Caritas Children”, between Austria and Portugal (1947-1958)», which was aimed to understand the way the Action took place, its repercussions on those involved, the way it was dealt with by government agencies and displayed by the press at its service and perceived by the population.